Controlling siltation in dug-out ponds - Soil-Water Management Research Group (International Water Management Institute, 2005)
Manual produced under the IWMI financed project "Options for Increasing the Productivity of Harvested and Stored Rainwater for Smallholder Farmers in the Dry Area of Western Pare Lowlands?